Ultrasonic coupling material composition, ultrasonic coupling material film and ultrasonography
A silicone-based ultrasonic coupling material composition addresses the limitations of existing materials by maintaining high ultrasonic performance and avoiding skin residues, ensuring effective and comfortable long-term use in wearable devices.
Patent Information
- Application Number
- JP2024101654
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-12
- Filing Date
- 2024-06-25
- Publication Date
- 2025-01-24
AI Technical Summary
Existing ultrasonic coupling materials for long-term wear applications are unable to maintain high ultrasonic transmittance and sensitivity, leave residues on the skin, and cause skin roughness due to their water-soluble or water-insoluble nature, which limits their usability in wearable devices for continuous ultrasonic measurements.
A composition comprising a silicone adhesive and silicone oil without crosslinking points, combined with a resin and an organic solvent, forms a film that adheres to the skin, filling unevenness and maintaining ultrasonic transmission and sensitivity, even when wet or dry, without leaving residues.
The film provides excellent biocompatibility, maintains ultrasonic performance under varying conditions, is lightweight, and does not cause skin irritation or residue, making it suitable for long-term wear in ultrasonic examinations.
Smart Images

Figure 2025013209000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an ultrasonic coupling material composition, an ultrasonic coupling material film, and an ultrasonic inspection method. [Background technology]
[0002] In recent years, the development of wearable devices has progressed with the spread of IoT (Internet of Things). Typical examples are watches and glasses that can connect to the Internet. In addition, wearable devices that can constantly monitor the condition of the body are needed in the medical and sports fields, and these are expected to be growth fields in the future.
[0003] For example, a watch-type wearable device equipped with an optical sensor, a capacitance sensor, an ultrasonic sensor, a pressure sensor, etc. has been proposed (Patent Document 1).
[0004] Wearable devices capable of ultrasound diagnosis are also being considered, which would make it possible to visualize the state of internal organs and blood vessels and constantly measure pulse and blood pressure (Patent Document 2).
[0005] In an ultrasonic diagnostic device, an ultrasonic probe (probe) is placed in close contact with the skin, and ultrasonic waves emitted from the surface of the probe through an ultrasonic transmitter bounce off inside the body, and information about the inside of the body can be detected by a receiver through the probe. During ultrasonic measurement, if the surface to be measured is uneven and the surface of the ultrasonic probe cannot cover the unevenness of the surface to be measured and an air layer exists, the ultrasonic waves emitted from the surface of the ultrasonic probe are reflected by the air layer and do not reach the inside of the body. Therefore, during ultrasonic diagnosis, a water-soluble gel-based coupling material is inserted between the surface of the ultrasonic probe and the skin (Patent Document 3). Patent Document 4 lists many water-soluble coupling materials as examples.
[0006] For one-time ultrasound measurements, a water-soluble gel-based coupling material is applied to the skin, an ultrasound probe is placed on top of the material, and the measurement is performed. After the measurement, the gel on the skin surface can be wiped off with a cloth or paper soaked in water, or washed away with water. However, if the ultrasound probe is attached for a long period of time, the water-soluble gel dissolves if the probe is left attached while exercising or showering or bathing, and if the coupling material disappears, ultrasound signals cannot be received, so there is a problem that gel-based coupling materials cannot be used for long-term wear.
[0007] For this reason, water-insoluble coupling materials have been proposed, such as paraffin-based materials (Patent Document 5) and silicone gel-based materials (Patent Document 6).
[0008] If the coupling is a water-soluble gel, it can be easily removed after measurement as described above, but if paraffin or silicone remains on the skin, it is not easy to remove it by wiping with paper or cloth soaked in paraffin oil, etc. Silicone gel is a low-crosslinked silicone rubber, but if silicone oil is added to it, the silicone oil may remain on the skin, and it is necessary to remove the remaining silicone oil after peeling it off.
[0009] Therefore, there is a demand for a coupling material for ultrasonic measurement that is water-insoluble for long-term wear applications, and there is a need to develop a coupling material that leaves no residue on the skin when the coupling material is removed from the skin after ultrasonic measurement, covers the unevenness of the skin, and has high ultrasonic transparency and sensitivity. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Patent Publication No. 2021-093127 [Patent Document 2] International Publication No. 2020 / 049934 [Patent Document 3] Japanese Unexamined Patent Publication No. 46-000146 [Patent Document 4] Special Publication No. 2005-532871 [Patent Document 5] Japanese Patent Publication No. 63-019135 [Patent Document 6] U.S. Patent No. 9,211,106 Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made to solve the above problems, and aims to provide an ultrasonic coupling material composition, an ultrasonic coupling material film, and an ultrasonic inspection method which can be used to produce an ultrasonic coupling material film that fills in unevenness in the skin, has high ultrasonic transmission and sensitivity, and is excellent in biocompatibility, is lightweight, and is low-cost, does not significantly decrease in ultrasonic transmission whether it is wet or dry, is soft and has excellent elasticity, leaves no residue on the skin after peeling, and does not cause rough skin. [Means for solving the problem]
[0012] In order to solve the above problems, the present invention provides an ultrasonic coupling material composition containing (A) a silicone pressure-sensitive adhesive and (B) a silicone oil having no crosslinking points, The (A) silicone pressure-sensitive adhesive comprises: (a) a diorganopolysiloxane having a viscosity of 100,000 mPa s or more at 25°C; R 1 3SiO 1 / 2 and resin having SiO2 units (R 1 is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.) and a resin composition (b) containing an organic solvent, The silicone oil (B) having no crosslinking points has a kinetic viscosity at 25° C. of 10 to 100,000 mm 2 Silicone oil that does not have crosslinking points in the range of / s The ultrasonic coupling material composition is characterized in that
[0013] Such an ultrasonic coupling material composition can fill in unevenness in the skin, has high ultrasonic transmission and sensitivity, is excellent in biocompatibility, is lightweight, and can produce an ultrasonic coupling material film at low cost. The ultrasonic transmission does not decrease significantly whether the material is wet or dry, is soft and has excellent elasticity, leaves no residue on the skin after peeling, and does not cause rough skin.
[0014] In the present invention, the diorganopolysiloxane (a) is preferably a diorganopolysiloxane (a1) having an alkenyl group.
[0015] If such a diorganopolysiloxane (a) is contained, the alkenyl groups become crosslinking points, so that a preferable ultrasonic coupling material film can be formed.
[0016] In this case, it is preferable that the component (C) further contains an organohydrogenpolysiloxane having a SiH group, and it is even more preferable that the component (C) further contains a platinum-based catalyst.
[0017] The diorganosiloxane (a1) having an alkenyl group and the organohydrogenpolysiloxane (C) having a plurality of SiH groups can be crosslinked by an addition reaction in the presence of a platinum catalyst.
[0018] In this case, it is preferable that the value obtained by dividing the number of moles of SiH groups in the component (C) by the number of moles of alkenyl groups in the component (A) is in the range of 0.5 to 20.
[0019] With such a composition, a preferred ultrasonic coupling material film can be obtained by an addition curing reaction.
[0020] In the present invention, the component (B) is preferably a linear or branched diorganopolysiloxane that is free of alkenyl groups and SiH groups.
[0021] In the present invention, such a component (B) is preferred.
[0022] In addition, it is preferable that the mass of the component (B) divided by the total mass of the solid content of the components (a) and (b) and the components (B) and (C) is in the range of 0.2 to 0.8.
[0023] By setting the mass of component (B) within this range, a preferable ultrasonic coupling material film can be obtained.
[0024] Furthermore, it is preferable that the composition contains 0.1 to 10 parts by mass of dry silica per 100 parts by mass of the total of the solid contents of the components (a) and (b), the components (B) and (C).
[0025] By including dry silica in the composition of the present invention, the strength of the obtained ultrasonic coupling material film is improved, the film is less likely to tear when peeled from the release liner, and it is easier to apply to the skin or an ultrasonic probe.
[0026] The present invention also provides an ultrasonic coupling material film comprising a cured product of the ultrasonic coupling material composition.
[0027] The ultrasonic coupling material film of the present invention fills in unevenness in the skin, has high ultrasonic transmission and sensitivity, is excellent in biocompatibility, is lightweight, does not significantly decrease in ultrasonic transmission whether wet or dry, is soft and has excellent elasticity, leaves no residue on the skin after peeling, and does not cause rough skin.
[0028] In this case, the thickness of the ultrasonic coupling material film is preferably in the range of 10 to 10,000 μm.
[0029] When the film thickness is within the above range, the effects of excellent ultrasonic transmission and sensitivity, light weight, excellent flexibility and elasticity, no residue remaining on the skin after peeling off, and no skin roughness are further enhanced.
[0030] The present invention also provides a single ultrasonic coupling material film, characterized in that the ultrasonic coupling material film is a free-standing film that is separate and independent from a support.
[0031] The ultrasonic coupling material film of the present invention can also be used as a free-standing film (single film), and is easy to handle in ultrasonic testing.
[0032] The present invention also provides a laminated structure comprising a support and the ultrasonic coupling material film directly on and in contact with the support.
[0033] The ultrasonic coupling material film of the present invention can be used as a free-standing film, but can also be used as a structure in which the ultrasonic coupling material film is laminated on a support (laminated structure), which is easy to handle in ultrasonic inspection.
[0034] The present invention also provides a method for forming a laminate structure, which comprises applying the ultrasonic coupling material composition onto a release liner film, heating and curing the composition to form an ultrasonic coupling material film, peeling the release liner film from the ultrasonic coupling material film, attaching the ultrasonic coupling material film onto another support, and attaching an ultrasonic probe to the surface opposite to the surface in contact with the other support to form a laminate structure. In addition, the ultrasonic coupling material composition can be applied onto a release liner film, heated and cured to form an ultrasonic coupling material film, and then the release liner film can be peeled off from the ultrasonic coupling material film and attached to an ultrasonic probe to form a laminate structure. Alternatively, the ultrasonic coupling material composition can be applied onto an ultrasonic probe, heated and cured to form an ultrasonic coupling material film to form a laminate structure.
[0035] In the present invention, the ultrasonic coupling material composition can be applied onto a release liner film or an ultrasonic probe, and then heated and cured before use, so that a laminate structure can be formed by selecting the desired form as described above in ultrasonic testing.
[0036] The present invention also provides an examination method (excluding methods for surgery, treatment, or diagnosis of humans) characterized in that, following the above-mentioned method for forming a laminated structure, the ultrasonic probe is attached to the skin with the surface on which the ultrasonic coupling material film is formed, and an ultrasonic examination is performed.
[0037] The ultrasonic coupling material film formed using the ultrasonic coupling material composition of the present invention has excellent ultrasonic transmittance and sensitivity, as well as excellent water resistance, and leaves no residue on the skin after measurement, reducing the burden on the subject, making it extremely useful in various ultrasonic examinations, such as for long-term wearing applications. Effect of the Invention
[0038] As described above, the ultrasonic coupling material composition of the present invention fills in unevenness in the skin, has high ultrasonic transmission and sensitivity, is excellent in biocompatibility, is lightweight, and can be manufactured at low cost. Its ultrasonic transmission does not decrease significantly whether it is wet or dry, is soft and has excellent elasticity, leaves no residue on the skin after peeling, and does not cause rough skin. [Brief description of the drawings]
[0039] [Figure 1] FIG. 2 is a schematic cross-sectional view showing an example of a coupling material film of the present invention. [Diagram 2] FIG. 4 is a schematic cross-sectional view showing another example of the coupling material film of the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing an example of use in which the coupling material film of the present invention is attached to the skin. [Figure 4] FIG. 2 is a schematic cross-sectional view showing an example of use in which the coupling material film of the present invention is attached onto an ultrasonic probe. [Diagram 5] FIG. 1 is a schematic cross-sectional view showing an example of use in which a coupling material film of the present invention is attached between an ultrasonic probe and the skin. [Figure 6] FIG. 1 is a schematic cross-sectional view showing an example of ultrasonic diagnosis performed with the coupling material film of the present invention attached between an ultrasonic probe and the skin. [Figure 7]FIG. 1 is a schematic cross-sectional view showing an example of ultrasonic diagnosis performed with a conventional coupling material film attached between an ultrasonic probe and the skin. [Figure 8] 1 is a photograph of a coupling material film of the present invention attached to an arm. [Figure 9] 1 is a photograph of the water-soluble gel grease of Comparative Example 5 dispensed onto an arm. [Figure 10] This is a photograph of a handheld ultrasound diagnostic device (apparatus) viewed from the ultrasound probe side. [Figure 11] This is a photograph showing the ultrasonic coupling material film in the cross-sectional state of Figure 1 being attached to an ultrasonic probe while peeling off the release liner. [Figure 12] This is a photograph showing ultrasonic diagnosis performed with an ultrasonic measuring device placed on a coupling material film. [Figure 13] 1 is a photograph of an ultrasound image when an ultrasound signal is being acquired satisfactorily. [Figure 14] 1 is a photograph of an ultrasound image when the ultrasound signal is not being acquired properly. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] As described above, there has been a need for the development of a coupling material composition that is water-insoluble, has excellent ability to fill skin irregularities, is excellent in sound transmission and biocompatibility, is lightweight and can be produced at low cost, is soft, stretchable and strong, and can be in contact with the skin for long periods of time and can stably collect ultrasonic signals even when wetted by bathing or sweating or when dried; a coupling laminate film thereof; and an ultrasonic measurement method thereof.
[0041] Silicone materials are examples of coupling materials that are water-insoluble, have excellent sound transmission properties, and are biocompatible. The aforementioned Patent Document 6 shows a coupling material that uses silicone gel. Silicone gel is a very soft silicone rubber with ultra-low density crosslinking. However, being soft alone is not enough to fill in the micron-sized irregularities of soft skin.
[0042] In order to further soften the silicone gel, as described in JP 2015-028178 A, a method of adding non-crosslinked silicone oil or hydrocarbon mineral oil can be mentioned. The addition of non-crosslinked silicone oil improves the embedding property of the skin unevenness, and when used as an ultrasonic coupling material, the sensitivity of ultrasonic measurement is improved. However, when a large amount of non-crosslinked silicone oil is added, it bleeds out, and when the coupling material film is peeled off from the skin after the ultrasonic measurement is finished, silicone oil residue is generated on the skin. If silicone oil residue is present, it is necessary to wipe the skin with a towel or absorbent cotton soaked in mineral oil to remove it, which is not preferable because it is time-consuming.
[0043] As a result of extensive research into the above-mentioned problems, the inventors came up with the idea of using a silicone adhesive as the base, rather than a silicone gel, in order to prevent bleeding out even when a large amount of non-crosslinked silicone oil is added. This silicone adhesive is made of a crosslinkable silicone and R 1 3SiO 1 / 2 and a reaction product or mixture of an MQ resin having SiO2 units, which prevents non-crosslinked silicone oil from bleeding out. The present inventors found that the above-mentioned problems can be solved by an ultrasonic coupling material composition containing such a silicone pressure sensitive adhesive and a silicone oil having no crosslinking points, and completed the present invention.
[0044] That is, the present invention provides an ultrasonic coupling material composition containing (A) a silicone pressure-sensitive adhesive and (B) a silicone oil having no crosslinking points, The (A) silicone pressure-sensitive adhesive comprises: (a) a diorganopolysiloxane having a viscosity of 100,000 mPa s or more at 25°C; R 1 3SiO 1 / 2 and resin having SiO2 units (R 1 is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.) and a resin composition (b) containing an organic solvent, The silicone oil (B) having no crosslinking points has a kinetic viscosity at 25° C. of 10 to 100,000 mm 2 Silicone oil that does not have crosslinking points in the range of / s The ultrasonic coupling material composition is characterized in that
[0045] Thus, the present invention relates to a coupling material film that is inserted between the skin and an ultrasonic diagnostic device that is used to contact the skin of a living body, visualize the condition of internal organs and blood vessels, and measure pulse and blood pressure, a coupling material composition that provides this, and a method for producing the coupling material film.
[0046] The present invention will be described in detail below, but the present invention is not limited thereto.
[0047] <Ultrasonic coupling material composition> The ultrasonic coupling material composition of the present invention contains a silicone pressure sensitive adhesive, a silicone oil having no crosslinking sites, and an organic solvent. In the ultrasonic coupling material composition of the present invention, the silicone pressure-sensitive adhesive (A) is a mixture of the components (a) and (b) or a mixture of a condensation reaction product and an organic solvent, and the component (a) is a diorganopolysiloxane and the component (b) is R 1 3SiO 1 / 2 It is made of a resin having SiO2 units and an organic solvent, and has a dynamic viscosity of 10 to 100,000 mm at 25°C. 2 It is preferable that the composition contains a silicone oil (B) component that does not have a crosslinking point in the range of R / s, an organohydrogenpolysiloxane (C) component, and a platinum-based catalyst. 1 is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms. Each component will be described in more detail below.
[0048] [Component (A)] (A) The silicone adhesive is a mixture of diorganopolysiloxane (a) having a viscosity of 100,000 mPa s or more at 25°C and R 1 3SiO 1 / 2 and resin having SiO2 units (R1 is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.) and a resin composition (b) containing an organic solvent.
[0049] (Component (a)) The component (a) blended in the ultrasonic coupling material composition of the present invention is a diorganopolysiloxane having a viscosity of 100,000 mPa·s or more at 25°C, and is not particularly limited as long as it is such, but is preferably a diorganopolysiloxane (a1) having an alkenyl group. As the diorganopolysiloxane having an alkenyl group, a diorganopolysiloxane corresponding to the component (A1) described in JP 2015-193803 A and having a viscosity of 100,000 mPa·s or more at 25°C can be used.
[0050] Examples of the alkenyl group include a vinyl group, an allyl group, a hexenyl group, an octenyl group, an acryloylpropyl group, an acryloylmethyl group, a methacryloylpropyl group, and a vinyloxypropyl group, with the vinyl group being particularly preferred.
[0051] Groups other than alkenyl groups are substituted or unsubstituted monovalent hydrocarbon groups having 1 to 10 carbon atoms. Specific examples include alkyl groups such as methyl, ethyl, propyl and butyl groups, cycloalkyl groups such as cyclohexyl groups, aryl groups such as phenyl and tolyl groups, and groups in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups have been substituted with other groups such as halogen, amino, hydroxyl or cyano groups, for example, 3-aminopropyl, 3,3,3-trifluoropropyl, 3-hydroxypropyl and 3-cyanopropyl groups. Methyl and phenyl groups are particularly preferred.
[0052] Furthermore, component (a) may contain diorganopolysiloxane (a2) that corresponds to component (A2) described in JP 2015-193803 A, has a viscosity of 100,000 mPa·s or more at 25°C, and does not have an alkenyl group. The ends of the polymers A1 and A2 may be hydroxyl or alkoxy groups, and may be bonded by condensation reaction with the silanol groups in the MQ resin of component (b). In this case, components (a) and (b) are not independent components, but are integrated components. The condensation reaction can be carried out by heating using an acid catalyst or an alkaline catalyst.
[0053] The polysiloxanes a1 and a2 may be linear or branched.
[0054] Examples of adhesive silicone resins include those that cure by addition reaction or radical crosslinking reaction. In the addition curing type, alkenyl groups and SiH groups crosslink by addition reaction, while in the radical curing type, crosslinking proceeds not only when alkenyl groups are present but also when they are not. In this case, crosslinking with the silicone oil (B) component that does not have a crosslinking group may also occur. This may reduce the fluidity of the silicone oil, reducing its ability to embed in the skin and its sensitivity as an ultrasonic coupling material. For this reason, the addition curing type is preferable to the radical crosslinking type.
[0055] Also, as component (a), a modified siloxane having a group selected from an amino group, an oxirane group, an oxetane group, a polyether group, a hydroxyl group, a carboxyl group, a mercapto group, a methacryl group, an acrylic group, a phenol group, a silanol group, a carboxylic anhydride group, an aryl group, an aralkyl group, an amide group, an ester group, and a lactone ring can be added. The modified siloxane may be one in which one end, both ends, or a side chain of the siloxane is modified.
[0056] Reducing the amount of octamethylcyclotetrasiloxane and decamethylcyclopentasiloxane in component (a) is effective for reducing skin irritation. A method for reducing this is described in JP 2015-193803 A.
[0057] The components (a1) and (a2) may be either oil-like or raw rubber-like. In the case of raw rubber-like composition, when the viscosity is as high as more than 500,000 mPa·s, the viscosity when dissolved in toluene to a concentration of 30% by mass (30% by mass soluble viscosity) is preferably 100,000 mPa·s or less. Furthermore, the 30% by mass soluble viscosity is preferably 1,000 to 60,000 mPa·s. If the 30% by mass soluble viscosity exceeds 100,000 mPa·s, the composition becomes too viscous, making stirring during production difficult. In the present invention, the viscosity (absolute viscosity) is a value measured at 25°C using a rotational viscometer.
[0058] [(b) component] (b) Component is R 1 3SiO 1 / 2 and resin having SiO2 units (R 1 is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.) and an organic solvent.
[0059] The resin in component (b) is R 1 3SiO 1 / 2 It is a so-called MQ resin that has SiO2 units (M units) and SiO2 units (Q units), and is dissolved in an organic solvent. 1 is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms. As the organic solvent for dissolving the MQ resin, an appropriate organic solvent described below may be selected.
[0060] R 1is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, examples of which include alkyl groups such as methyl, ethyl, propyl and butyl, cycloalkyl groups, aryl groups such as phenyl, and alkenyl groups such as vinyl, allyl and hexenyl.Further examples include those in which some or all of the hydrogen atoms bonded to the carbon atoms of these groups have been substituted with other groups such as halogen, amino, hydroxyl or cyano groups, for example, 3-aminopropyl, 3,3,3-trifluoropropyl, 3-hydroxypropyl and 3-cyanopropyl.
[0061] Preferably, R 1 3SiO 1 / 2 The ratio of the number of units / SiO2 units is 0.6 to 1.7. If the ratio of the number is equal to or more than the lower limit, the adhesive strength and tackiness are not reduced, and if it is equal to or less than the upper limit, the adhesive strength and holding power are good.
[0062] Component (b) may have OH groups, and the OH group content is preferably 0.01 to 4.0 mass% of the total mass of component (B). If the OH group content is above the lower limit, the cohesive strength of the adhesive is high, and if it is below the upper limit, the tack of the adhesive does not decrease. The MQ resin of component (b) usually has silanol groups, and these silanol groups can form chemical bonds by condensation reaction with the hydroxyl or alkoxy terminal groups of the diorganopolysiloxane in component (a).
[0063] Two or more kinds of (b) components may be used in combination. 1 SiO 3 / 2 Units (T units) and / or R 1 It is also possible to incorporate 2SiO units (D units) in component (b).
[0064] The presence of component (b) imparts adhesive properties, preventing component (B) from bleeding out and from remaining on the skin after the coupling material is removed.
[0065] The ratio of solids of component (a) and component (b) (the ratio of things other than the organic solvent in component (A)) can be 20 to 100 parts by mass of component (a) per 120 parts by mass of the entire component (A), while the ratio of component (b) can be 1 to 20 parts by mass.
[0066] [(B) Component] Component (B) is a silicone oil that does not have a crosslinking point (non-crosslinked type) and has a kinetic viscosity at 25°C of 10 to 100,000 mm 2 / s, preferably 50 to 50,000 mm 2 In the present invention, the kinematic viscosity is a value measured at 25° C. using an Ostwald viscometer.
[0067] Component (B) is a fluid oil by itself, and by adding component (B), it is possible to fill in the minute irregularities in the skin when the ultrasonic coupling material film is attached to the skin, thereby improving the transmittance of ultrasonic waves.
[0068] The non-crosslinked silicone oil of component (B) is not particularly limited as long as it has a kinetic viscosity at 25°C within the above range, but is preferably a linear or branched diorganopolysiloxane having no alkenyl groups or SiH groups. Such component (B) has good affinity with the silicone pressure-sensitive adhesive (A), and in particular, even if a large amount of non-crosslinked silicone oil is added, it does not bleed out, making it possible to prevent the oil from bleeding out.
[0069] The mass of component (B) divided by the total mass of the solid contents of components (a), (b), (B) and (C) (total mass of the solid contents of components (A) to (C)) is preferably in the range of 0.2 to 0.8 (0.20 to 0.80), and more preferably in the range of 0.3 to 0.78.
[0070] [(C) component] The component (C) is an organohydrogenpolysiloxane having a SiH group. When the silicone adhesive has an alkenyl group, the alkenyl group and the SiH group undergo crosslinking (addition curing) by addition reaction (hydrosilylation reaction), and in this case, the component (C) can function as a crosslinking agent. The component (C) is not particularly limited as long as it is an organohydrogenpolysiloxane having a SiH group, and for example, the component (C) described in JP 2015-193803 A (having two or more SiH groups, preferably three or more SiH groups in the molecule) can be used. The viscosity of component (C) at 25°C is preferably 1 to 1,000 mPa·s, and more preferably 2 to 500 mPa·s. Component (C) may be a mixture of two or more kinds. It may have a linear, branched, or cyclic structure. The number of SiH groups in one molecule of the organohydrogenpolysiloxane is preferably two or more, and more preferably three or more. Such a component (C) is preferred when the composition is of the addition cure type. When the MQ resin of component (b) has SiH groups, component (C) is not necessarily required.
[0071] The diorganosiloxane (a1) having an alkenyl group and the organohydrogenpolysiloxane (C) having a plurality of SiH groups can be crosslinked by an addition reaction using a platinum catalyst. The ratio of the number of moles of SiH groups divided by the number of moles of alkenyl groups is preferably in the range of 0.5 to 20, more preferably in the range of 1 to 15.
[0072] Examples of platinum catalysts include platinum catalysts such as chloroplatinic acid, alcohol solutions of chloroplatinic acid, reaction products of chloroplatinic acid and alcohol, reaction products of chloroplatinic acid and olefin compounds, reaction products of chloroplatinic acid and vinyl group-containing siloxane, platinum-olefin complexes, platinum-vinyl group-containing siloxane complexes, platinum group metal catalysts such as rhodium complexes and ruthenium complexes, etc. Furthermore, these catalysts may be used in the form of a solution or dispersion in an alcohol-based, hydrocarbon-based, or siloxane-based solvent.
[0073] The amount of platinum catalyst added is preferably in the range of 5 to 2,000 ppm, particularly 10 to 500 ppm (metal mass equivalent), per 100 parts by mass of the resin solution (ultrasonic coupling material composition) made by combining (A), (B), (C) and the organic solvent.
[0074] When an addition-curing silicone resin is used, an addition reaction inhibitor may be added as a quencher to prevent the platinum catalyst from acting in the solution and in a low-temperature environment before heat curing after coating formation. Specific examples include 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynylcyclohexanol, 3-methyl-3-trimethylsiloxy-1-butyne, 3-methyl-3-trimethylsiloxy-1-pentyne, 3,5-dimethyl-3-trimethylsiloxy-1-hexyne, 1-ethynyl-1-trimethylsiloxycyclohexane, bis(2,2-dimethyl-3-butynoxy)dimethylsilane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and 1,1,3,3-tetramethyl-1,3-divinyldisiloxane.
[0075] The amount of the addition reaction inhibitor added is preferably in the range of 0 to 10 parts by mass, and particularly preferably 0.05 to 3 parts by mass, per 100 parts by mass of the resin solution.
[0076] [Silica particles] Dry silica particles can also be added to the composition of the present invention. By adding dry silica, the strength of the ultrasonic coupling material film is improved, the film is less likely to tear when peeled off from the release liner, and it is easier to apply to the skin or ultrasonic probe. The specific surface area of the dry silica is 50 to 500 m. 2 / g range, 100-400m 2 / g is preferred. The specific surface area may be measured by the BET method. Silica in which the silanol on the silica surface is replaced with a trimethylsilyl group, a dimethylsilyl group, or a dimethyl silicone is preferred because of its high dispersibility. As the dry silica, a commercially available product may be used, for example, AEROSIL RX200 (manufactured by Nippon Aerosil). The amount of dry silica added is preferably 0.1 to 10 parts by mass per 100 parts by mass of the total of the solid contents of components (a), (b), (B) and (C) (total solid contents of components (A) to (C)).
[0077] [Organic solvents] In addition to the organic solvent contained in the component (b), the composition of the present invention may further contain the same or another organic solvent. By adjusting the type and amount of the organic solvent contained in the composition of the present invention, the workability can be improved. The organic solvent is not particularly limited, but the following can be mentioned: toluene, xylene, cumene, 1,2,3-trimethylbenzene, 1,2,4-trimethylbenzene, 1,3,5-trimethylbenzene, styrene, α-methylstyrene, butylbenzene, sec-butylbenzene, isobutylbenzene, cymene, diethylbenzene, 2-ethyl-p-xylene, 2-propyltoluene, 3-propyltoluene, 4-propyltoluene, 1,2,3,5-tetramethyltoluene, 1,2,4,5-tetramethyltoluene, tetrahydronaphthalene, 4-phenyl-1-butene, tert-butylbenzene, butylbenzene, cyclohexane ... Milbenzene, amylbenzene, 2-tert-butyltoluene, 3-tert-butyltoluene, 4-tert-butyltoluene, 5-isopropyl-m-xylene, 3-methylethylbenzene, tert-butyl-3-ethylbenzene, 4-tert-butyl-o-xylene, 5-tert-butyl-m-xylene, tert-butyl-p-xylene, 1,2-diisopropylbenzene, 1,3-diisopropylbenzene, 1,4-diisopropylbenzene, dipropylbenzene, pentamethylbenzene, hexamethylbenzene, Aromatic hydrocarbon solvents such as hexylbenzene and 1,3,5-triethylbenzene, n-heptane, isoheptane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, 1,6-heptadiene, 5-methyl-1-hexyne, norbornane, norbornene, dicyclopentadiene, 1-methyl-1,4-cyclohexadiene, 1-heptyne, 2-heptyne, cycloheptane, cycloheptene, 1,3-dimethylcyclopentane, ethylcyclopentane, methylcyclohexane, 1-methyl-1-cyclohexene, 3- Methyl-1-cyclohexene, methylenecyclohexane, 4-methyl-1-cyclohexene, 2-methyl-1-hexene, 2-methyl-2-hexene, 1-heptene, 2-heptene, 3-heptene, n-octane, 2,2-dimethylhexane, 2,3-dimethylhexane, 2,4-dimethylhexane, 2,5-dimethylhexane, 3,3-dimethylhexane, 3,4-dimethylhexane, 3-ethyl-2-methylpentane, 3-ethyl-3-methylpentane, 2-methylheptane, 3-methylheptane, 4-methylheptane, 2,2,3-trimethylpentane, 2,2,4-trimethylpentane, cyclooctane, cyclooctene, 1,2-dimethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, ethylcyclohexane, vinylcyclohexane, isopropylcyclopentane, 2,2-dimethyl-3-hexene, 2,4-dimethyl-1-hexene, 2,5-dimethyl-1-hexene, 2,5-dimethyl-2-hexene, 3,3-dimethyl-1-hexene, 3,4-dimethyl-1-hexene, 4,4-dimethyl -1-hexene, 2-ethyl-1-hexene, 2-methyl-1-heptene, 1-octene, 2-octene, 3-octene, 4-octene, 1,7-octadiene, 1-octyne, 2-octyne, 3-octyne, 4-octyne, n-nonane, 2,3-dimethylheptane, 2,4-dimethylheptane, 2,5-dimethylheptane, 3,3-dimethylheptane, 3,4-dimethylheptane, 3,5-dimethylheptane, 4-ethylheptane, 2-methyloctane, 3-methyloctane, 4-methyloctane, 2,2,4,4- Tetramethylpentane, 2,2,4-trimethylhexane, 2,2,5-trimethylhexane, 2,2-dimethyl-3-heptene, 2,3-dimethyl-3-heptene, 2,4-dimethyl-1-heptene, 2,6-dimethyl-1-heptene, 2,6-dimethyl-3-heptene, 3,5-dimethyl-3-heptene, 2,4,4-trimethyl-1-hexene, 3,5,5-trimethyl-1-hexene, 1-ethyl-2-methylcyclohexane, 1-ethyl-3-methylcyclohexane, 1-ethyl-4-methylcyclohexa cyclohexane, propylcyclohexane, isopropylcyclohexane, 1,1,3-trimethylcyclohexane, 1,1,4-trimethylcyclohexane, 1,2,3-trimethylcyclohexane, 1,2,4-trimethylcyclohexane, 1,3,5-trimethylcyclohexane, allylcyclohexane, hydrindane, 1,8-nonadiene, 1-nonyne, 2-nonyne, 3-nonyne, 4-nonyne, 1-nonene, 2-nonene, 3-nonene, 4-nonene, n-decane, 3,3-dimethyloctane, 3,5-dimethyloctane, 4,4-Dimethyloctane, 3-ethyl-3-methylheptane, 2-methylnonane, 3-methylnonane, 4-methylnonane, tert-butylcyclohexane, butylcyclohexane, isobutylcyclohexane, 4-isopropyl-1-methylcyclohexane, pentylcyclopentane, 1,1,3,5-tetramethylcyclohexane, cyclododecane, 1-decene, 2-decene, 3-decene, 4-decene, 5-decene, 1,9-decadiene, decahydronaphthalene, 1-decene, 2-decene, 3-decene, 4-decene, 5-decene, 1,5,9-decatriene, 2 ,6-Dimethyl-2,4,6-octatriene, limonene, myrcene, 1,2,3,4,5-pentamethylcyclopentadiene, α-phellandrene, pinene, terpinene, tetrahydrodicyclopentadiene, 5,6-dihydrodicyclopentadiene, dicyclopentadiene, 1,4-decadiyne, 1,5-decadiyne, 1,9-decadiyne, 2,8-decadiyne, 4,6-decadiyne, n-undecane, amylcyclohexane, 1-undecene, 1,10-undecadiene, 1-undecyne, 3-undecyne, 5-undecyne, tricyclo[6.2.1.0, 2,7 ]Aliphatic hydrocarbon solvents such as undec-4-ene, n-dodecane, n-tridecane, n-pentadecane, n-hexadecane, 2-methylundecane, 3-methylundecane, 4-methylundecane, 5-methylundecane, 2,2,4,6,6-pentamethylheptane, 1,3-dimethyladamantane, 1-ethyladamantane, 1,5,9-cyclododecatriene, 1,2,4-trivinylcyclohexane, and isoparaffin can be mentioned. These may be any mixtures.
[0078] The hydrocarbon solvent is an aliphatic solvent, not including an aromatic solvent, and more specifically, it is preferable that the solvent is mainly normal paraffins, isoparaffins, naphthenes, or a mixture thereof. Normal paraffins and isoparaffins have less odor than naphthenes, so it is preferable to use normal paraffins, isoparaffins, or a mixture of both, since the odor can be reduced to an extreme extent and the burden on the environment and human body can be reduced. Here, normal paraffins, isoparaffins, or a mixture of both means a highly refined solvent whose main component is normal paraffins, isoparaffins, or a mixture of both, but generally, even these very highly refined solvents contain trace amounts of naphthenes and aromatics ranging from ppm level to a maximum of about 0.5% or less (by mass). However, the effect of these trace components on the odor is very small and can be almost negligible. Thus, normal paraffins, isoparaffins or a mixture of both referred to herein means those which are substantially free of naphthenes and aromatics in amounts equal to or greater than the above-mentioned trace impurity levels.
[0079] Alternatively, a commercially available organic solvent may be used, such as ISOPAR M. TM M), "ISOPAR G" TM G) (ExxonMobil Corporation), "IP Solvent 2028" (Idemitsu Kosan), and branched paraffinic solvent mixtures, especially isoparaffinic hydrocarbons, such as "Exxsol D110" (Exxsol TM ) (ExxonMobil Corporation), and naphthenic hydrocarbons such as "AF Solvent No. 4" (ENEOS). The ISOPAR® series of isoparaffinic solvents are preferred. These are characterized by low reactivity, stability, low toxicity, high safety, and little odor.
[0080] The amount of the organic solvent added is preferably within a range of 10 to 50,000 parts by mass per 100 parts by mass of the total of the resins (a) and (b) (the solid content of the resin composition (b)).
[0081] [Other additives] In addition to the dry silica, wet silica, alumina particles, titania particles, zirconia particles, and pigments can be mixed into the ultrasonic coupling material composition of the present invention. Strength is improved by adding wet silica particles, alumina particles, titania particles, and zirconia particles. Pigments are added when coloring is required. Alumina particles, titania particles, and zirconia particles can be preferably used in either dry or wet form, and are more excellent in dispersibility when the surface is treated with a water-repellent silylating agent. The shape of the wet silica, alumina particles, titania particles, and zirconia particles may be any of spherical, elliptical, irregular, hollow, and porous.
[0082] <Ultrasonic coupling film> The ultrasonic coupling material film of the present invention comprises a cured product of the ultrasonic coupling material composition. In the present invention, the ultrasonic coupling material composition is used to form an ultrasonic coupling material film on a support such as a release liner film, and this can be inserted between the skin and the ultrasonic probe to transmit ultrasonic waves between the skin and the ultrasonic probe.
[0083] The ultrasonic coupling material (film) of the present invention will be described in detail below with reference to the drawings, but the present invention is not limited thereto.
[0084] Fig. 1 is a schematic cross-sectional view showing an example of an ultrasonic coupling material film of the present invention. The ultrasonic coupling material 1 in Fig. 1 shows a form formed on a release liner (support) 2.
[0085] The substrate of the release liner may be paper, plastic film made of plastic, glass, metal, cloth, etc. Examples of paper include fine paper, coated paper, art paper, glassine paper, polyethylene laminated paper, craft paper, Japanese paper, synthetic paper, etc. Examples of plastic films include polyethylene film, polypropylene film, polyester film, polyimide film, polyamide film, polyvinyl chloride film, polyvinylidene chloride film, polyvinyl alcohol film, polycarbonate film, polytetrafluoroethylene film, polystyrene film, ethylene-vinyl acetate copolymer film, ethylene-vinyl alcohol copolymer film, triacetyl cellulose film, polyether ether ketone film, polyphenylene sulfide film, etc. There is no particular restriction on the thickness or type of glass, and it may be chemically strengthened. Glass fiber can also be applied, and glass fiber may be used alone or in combination with other resins. Examples of cloth include natural fiber cloth, synthetic fiber cloth, and artificial leather, and examples of metal include aluminum foil, copper foil, gold foil, silver foil, nickel foil, etc. Among these, paper and plastic films are preferred, and polyester films are particularly preferred.
[0086] A fluorine-based release agent described in JP-A-2020-100763 and JP-A-2020-100764 can be applied to the base material of the release liner, thereby reducing the peel force.
[0087] <Method of manufacturing ultrasonic coupling material film> The method for producing the ultrasonic coupling material film of the present invention is not particularly limited, but a production example will be described below with reference to the drawings.
[0088] First, the ultrasonic coupling material composition of the present invention is applied onto a support (substrate) such as a release liner. The method of applying the ultrasonic coupling material composition onto a substrate such as a release liner is not particularly limited, but suitable methods include, for example, dip coating, spray coating, spin coating, bar coating, comma coating, slit coating, roll coating, flow coating, doctor coating, screen printing, flexographic printing, gravure printing, and inkjet printing.
[0089] Next, the ultrasonic coupling material composition applied onto the support (substrate) is cured. The method for curing the ultrasonic coupling material composition is not particularly limited, and for example, it is preferable to cure the applied film using either heat or light, or both.
[0090] The temperature when heating is not particularly limited, and is preferably, for example, about 50 to 250° C. Heating can be performed by electric heating methods such as hot air or a hot plate, or by heat generation methods such as irradiation with infrared rays or microwaves.
[0091] In addition, when heating and light irradiation, infrared radiation or microwave irradiation are combined, heating and light irradiation, infrared radiation or microwave irradiation may be performed simultaneously, heating may be performed after light irradiation, infrared radiation or microwave irradiation, or heating may be performed after light irradiation, infrared radiation or microwave irradiation. In addition, air drying may be performed before heating after coating in order to evaporate the solvent.
[0092] The thickness of the heat-cured ultrasonic coupling material film is preferably 10 to 10,000 μm, more preferably 10 to 4,000 μm, and even more preferably 20 to 3,000 μm. In each of the thickness ranges, the upper limit can be arbitrarily set to 5,000 μm, 2,000 μm, 500 μm, or 400 μm, and the lower limit can be arbitrarily set to 30 μm, 50 μm, 100 μm, or 120 μm, or these can be arbitrarily combined.
[0093] Rather than coating the ultrasonic coupling material composition on a release liner, the ultrasonic coupling material composition may be coated onto the ultrasonic probe.
[0094] As shown in Fig. 2, the ultrasonic coupling material film 1 can be sandwiched between release liners 2 on the top and bottom. This makes it easier to transport the adhesive ultrasonic coupling material film.
[0095] <How to use ultrasonic coupling material film> As shown in FIG. 3, the release liner 2 on one side of FIG. 2 can be peeled off, and the ultrasonic coupling material film 1 can be attached onto the skin 3.
[0096] As shown in FIG. 4, the ultrasonic coupling material film 1 can also be attached onto an ultrasonic probe 4 .
[0097] During ultrasonic diagnosis, as shown in FIG. 5, an ultrasonic coupling film 1 is sandwiched between the skin 3 and the ultrasonic probe 4.
[0098] In ultrasonic diagnosis, the state in which ultrasonic waves emitted from an ultrasonic probe are transmitted into the skin via an ultrasonic coupling film will be explained using Figures 6 and 7. Note that ultrasonic frequencies are generally sounds with frequencies of 3 MHz or higher that are used in ultrasonic diagnosis.
[0099] 6 is a schematic cross-sectional view of an ultrasonic coupling film 1 sandwiched between skin 3 and an ultrasonic probe 4. Since the ultrasonic coupling film 1 fills the unevenness of the skin 3, ultrasonic waves 5 emitted from the ultrasonic probe 4 are transmitted into the skin.
[0100] On the other hand, FIG. 7 is also a schematic cross-sectional view of an ultrasonic coupling material film 1 sandwiched between the skin 3 and the ultrasonic probe 4. However, in this case, the ultrasonic coupling material film 1 does not fill the unevenness of the skin 3, so the ultrasonic waves 5 are not transmitted into the skin.
[0101] FIG. 8 is a photograph showing the state after one side of the release liner has been peeled off, the ultrasonic coupling material film 1 has been applied to the skin on the inside of the forearm, and the other side of the release liner has been peeled off.
[0102] Figure 9 is a photograph of the state in which the water-soluble ultrasound coupling gel (water-soluble gel coupling material 6) is dispensed from a tube onto the skin on the inside of the forearm. After dispensing, it is spread with the fingers to form an ultrasound coupling material film.
[0103] FIG. 10 is a photograph of a handheld ultrasonic diagnostic device 10 viewed from the ultrasonic probe 4 side.
[0104] 11 is a photograph showing the ultrasonic coupling material film 1 being attached onto the ultrasonic probe of the ultrasonic diagnostic device 10 while peeling off the release liner 2. It can be seen that the ultrasonic coupling material film is an independent film.
[0105] FIG. 12 is a photograph showing a handheld ultrasonic diagnostic device placed on the coupling material film and measuring an ultrasonic image.
[0106] Figures 13 and 14 are the measured ultrasound images. Ultrasound diagnosis is performed by placing an ultrasound probe in close contact with the skin, and the ultrasound emitted from the surface of the probe via an ultrasound transmitter bounces off the body, and the information inside the body is detected by a receiver via the probe. When the ultrasound is transmitted inside the body and bounces off the target area, an ultrasound image such as that shown in Figure 13 can be obtained. On the other hand, if there is an air layer due to unevenness on the surface to be measured during ultrasound measurement, the ultrasound emitted from the surface of the ultrasound probe is reflected by the air layer and does not reach the inside of the body, resulting in a unclear ultrasound image as shown in Figure 14. In other words, as shown in Figure 6, when an ultrasonic coupling material film 1 is sandwiched between skin 3 and ultrasonic probe 4, and the ultrasonic coupling material film 1 fills the unevenness of skin 3, ultrasonic waves 5 are transmitted into the skin, resulting in an ultrasonic image as shown in Figure 13. On the other hand, if the ultrasonic coupling film 1 does not fill the unevenness of the skin 3 as shown in FIG. 7, the ultrasonic waves 5 are not transmitted into the skin, resulting in an ultrasonic image as shown in FIG. EXAMPLES
[0107] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited thereto. In the following, when the viscosity of the object to be measured is as high as more than 500,000 mPa·s, the viscosity when dissolved in toluene to a concentration of 30% by mass (30% solution viscosity) is shown. In other words, when the viscosity is shown by the 30% solution viscosity, it means that the viscosity of the object to be measured exceeds 500,000 mPa·s. The above absolute viscosity is a value at 25°C measured by a rotational viscometer.
[0108] [Examples 1 to 12, Comparative Examples 1 to 5] The components used in the examples and comparative examples are shown below.
[0109] (Component A (silicone adhesive)) (Component a) The viscosity of a 30% by mass toluene solution was 27,000 mPa·s, the alkenyl group content was 0.02 mol / 100 g, and the vinyl group-containing polydimethylsiloxane whose molecular chain ends were blocked with SiMe2Vi groups was designated as siloxane compound 1. The viscosity of a 30% by mass toluene solution was 27,000 mPa·s, the alkenyl group content was 0.01 mol / 100 g, and the vinyl group-containing polydimethylsiloxane whose molecular chain ends were blocked with SiMe2Vi groups was designated as siloxane compound 2. The viscosity of both siloxane compounds 1 and 2 as is at 25°C is 100,000 mPa·s or more.
[0110] (b component) Me3SiO 0.5 Polysiloxane (Me3SiO 0.5 A 60 mass% toluene solution of MQ resin (SiO2 unit / SiO2 unit = 0.8) was designated MQ resin 1. Me3SiO 0.5 Polysiloxane (Me3SiO 0.5 A 60 mass% hexane solution of MQ resin (SiO2 unit / SiO2 unit = 0.8) was designated MQ resin 2. Me3SiO 0.5 Polysiloxane (Me3SiO 0.5 A 60 mass% isoparaffin-based solvent ISOPAR (registered trademark) G solution (SiO2 unit / SiO2 unit = 0.8) was used as MQ resin 3.
[0111] (Component A (silicone adhesive)) 40 parts by mass of vinyl-containing polydimethylsiloxane whose molecular chain ends are capped with OH, whose viscosity in a 30% by mass toluene solution is 42,000 mPa s and whose alkenyl group content is 0.02 mol / 100 g, Me3SiO 0.5 Polysiloxane (Me3SiO 0.5 A solution consisting of 100 parts by mass of a 60% by mass toluene solution of 1,2-dichloro-2,4-diphenyl-2,4-tetramethylphenyl ...
[0112] (B component) As the non-crosslinked silicone oil, KF-96 manufactured by Shin-Etsu Chemical Co., Ltd. was used, as shown in Table 1. Its kinetic viscosity at 25°C corresponds to the number immediately before CS in the table. For example, the kinetic viscosity of "KF-96 1,000CS" is 1,000mm 2 / s, and the kinetic viscosity of "KF-96 100CS" is 100mm 2 The kinematic viscosity is measured at 25°C using an Ostwald viscometer.
[0113] (C component) As the methyl hydrogen silicone oil, KF-99 and KF-9901 manufactured by Shin-Etsu Chemical Co., Ltd. were used.
[0114] (Additives) Dry silica: AEROSIL RX200 (manufactured by Nippon Aerosil, surface-treated with trimethylsilyl groups)
[0115] (Organic solvent) ISOPAR TM G (Exxon Mobil Corporation)
[0116] The coupling material solutions (ultrasonic coupling material compositions) shown in Table 1 were mixed, and 100 parts by mass of this was added with 1 part by mass of platinum catalyst PL-56 manufactured by Shin-Etsu Chemical Co., Ltd., and further mixed.
[0117] [Table 1]
[0118] (Formation of coupling material film) The ultrasonic coupling material solution was applied onto the release liner of a PET separator SS1A (50 μm thick) manufactured by Nippa Corp. using a bar coater, and after 10 minutes of air drying, it was baked in a hot air oven at 125°C for 10 minutes to harden, forming the coupling material film shown in Figure 1. After hardening, a release liner of a PET separator SS1A (50 μm thick) manufactured by Nippa Corp. was placed over it, and the ultrasonic coupling material film sandwiched between the release liners shown in Figure 2 was created.
[0119] Comparative Example 5 In Comparative Example 5, a conventional grease-like water-soluble gel coupling material 6 was used as the ultrasonic coupling material.
[0120] (Measurement of the thickness of the biological contact layer) The thickness of the ultrasonic coupling material film prepared above was measured using a micrometer. The results are shown in Table 2.
[0121] One of the release liners was peeled off and the ultrasonic coupling material film surface was attached to the skin of the forearm. After it was attached to the skin, the other release liner was peeled off, forming an ultrasonic coupling material film on the skin as shown in Figure 8.
[0122] The gel ultrasonic coupling material of Comparative Example 5 was a grease-like water-soluble gel coupling material 6 that was applied to the arm as shown in Figure 9 and spread with the fingers to form a smooth film. It was not possible to measure the thickness of the coupling material film.
[0123] (Ultrasound signal measurement) A SONON 500L made by Healcerion was used as a handheld ultrasonic diagnostic device (ultrasound diagnostic meter) for measuring ultrasonic signals. As shown in Fig. 12, the probe surface of the ultrasonic diagnostic device was brought into contact with the ultrasonic coupling material film on the arm, and ultrasonic diagnosis was performed at a frequency of 8.5 MHz.
[0124] The coupling material was attached to the arm and the above-mentioned ultrasound diagnosis was performed, then the arm was immersed in water for 1 minute, then the arm was dried and ultrasound diagnosis was performed again.The coupling material film was then peeled off from the skin and visually observed to see if there was any residue on the skin.
[0125] (Water resistance evaluation) When ultrasonic diagnosis was performed after the water immersion, if a clear image such as that shown in FIG. 13 was obtained, it was judged as good, and if an unclear image such as that shown in FIG. 14 was obtained, it was judged as bad.
[0126] The evaluation results of the ultrasonic coupling materials listed in Table 1 are shown in Table 2. [Table 2]
[0127] As shown in Table 2, when the ultrasonic coupling material film shown in Examples 1 to 12, in which the silicone oil (B) component was added to the silicone adhesive consisting of the (a) component and the (b) component, was attached to the skin, a good ultrasonic image was obtained, and the same image was obtained even when the arm was immersed in water, and no residue was left on the skin after the ultrasonic coupling material film was peeled off from the skin. On the other hand, in the case of the silicone adhesive of Comparative Example 1, in which the (B) component was not added, the image obtained by ultrasonic diagnosis was poor. In the case of the silicone gel of Comparative Example 2, in which the MQ resin of the (b) component was not added, the ultrasonic image was good, but the silicone oil of the added (B) component was left behind after the film was peeled off from the skin. In Comparative Example 3, in which the kinetic viscosity of the (B) component was too large, the ultrasonic image was poor, and conversely, in Comparative Example 4, in which the kinetic viscosity of the (B) component was too small, the ultrasonic image was good, but residue was left behind after the ultrasonic coupling material film was peeled off from the skin. In the case of the conventional water-soluble gel coupling material of Comparative Example 5, the ultrasound image was good after application of the coupling material, but when the arm was immersed in water, the coupling material dissolved and the ultrasound image was poor.
[0128] The ultrasonic coupling material of the present invention can fill in the unevenness of the skin to provide a good ultrasonic image (i.e., it has high ultrasonic transmission and sensitivity), and is excellent in biocompatibility and lightweight because it is mainly composed of silicone. The ultrasonic coupling material composition (solution) of the present invention can be applied to a support as necessary and cured to produce an ultrasonic coupling material film at low cost. Since this ultrasonic coupling material film does not contain a water-soluble material, ultrasonic transmission does not decrease significantly even when it is wetted with water or dried. (A) Since it is a cured product derived from a silicone adhesive, it is soft and has excellent elasticity, does not leave any residue on the skin after peeling, and does not cause rough skin. Thus, the ultrasonic coupling material composition of the present invention has excellent characteristics.
[0129] The present specification includes the following aspects. [1]: An ultrasonic coupling material composition comprising (A) a silicone pressure sensitive adhesive and (B) a silicone oil having no crosslinking points, The (A) silicone pressure-sensitive adhesive comprises: (a) a diorganopolysiloxane having a viscosity of 100,000 mPa s or more at 25°C; R 1 3SiO 1 / 2 and resin having SiO2 units (R 1 is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.) and a resin composition (b) containing an organic solvent, The silicone oil (B) having no crosslinking points has a kinetic viscosity at 25° C. of 10 to 100,000 mm 2 Silicone oil that does not have crosslinking points in the range of / s 1. An ultrasonic coupling material composition comprising: [2]: The ultrasonic coupling material composition according to [1], wherein the diorganopolysiloxane (a) is a diorganopolysiloxane (a1) having an alkenyl group. [3]: The ultrasonic coupling material composition according to [2], further comprising, as component (C), an organohydrogenpolysiloxane having a SiH group. [4]: The ultrasonic coupling material composition according to [3], further comprising a platinum-based catalyst. [5]: The ultrasonic coupling material composition according to [4], wherein the value obtained by dividing the number of moles of SiH groups in the (C) component by the number of moles of alkenyl groups in the (A) component is in the range of 0.5 to 20. [6]: Any one of the ultrasonic coupling material compositions according to [2] to [5], characterized in that the (B) component is a linear or branched diorganopolysiloxane having no alkenyl groups or SiH groups. [7]: Any one of the ultrasonic coupling material compositions according to [3] to [6], characterized in that the mass of the (B) component divided by the total mass of the solid content of the (a) component and the (b) component and the (B) component is in the range of 0.2 to 0.8. [8]: Any one of the ultrasonic coupling material compositions of [3] to [7], further comprising 0.1 to 10 parts by mass of dry silica per 100 parts by mass of the total of the solid content of the (a) component and the (b) component, the (B) component and the (C) component. [9]: An ultrasonic coupling material film comprising a cured product of any one of the ultrasonic coupling material compositions [1] to [8].
[10] : The ultrasonic coupling material film according to [9], characterized in that the thickness of the ultrasonic coupling material film is in the range of 10 to 10,000 μm.
[11] : A single ultrasonic coupling material film, characterized in that the ultrasonic coupling material film of [9] or
[10] is a free-standing film that is separate and independent from the support.
[12] : A laminated structure comprising a support and the ultrasonic coupling material film of [9] or
[10] directly on the support.
[13] : A method for forming a laminate structure, comprising: applying any one of the ultrasonic coupling material compositions [1] to [8] onto a release liner film; heating and curing the composition to form an ultrasonic coupling material film; peeling the release liner film from the ultrasonic coupling material film; attaching the ultrasonic coupling material film to another support; and attaching an ultrasonic probe to the surface opposite to the surface in contact with the other support to form a laminate structure.
[14] : A method for forming a laminate structure, comprising: applying any one of the ultrasonic coupling material compositions of [1] to [8] onto a release liner film; heating and curing the composition to form an ultrasonic coupling material film; and then peeling the release liner film from the ultrasonic coupling material film and attaching the ultrasonic coupling material film to an ultrasonic probe to form a laminate structure.
[15] : A method for forming a laminate structure, comprising applying any one of the ultrasonic coupling material compositions according to [1] to [8] onto an ultrasonic probe, and heating and curing the composition to form an ultrasonic coupling material film to form a laminate structure.
[16] : A method for examination (excluding methods for surgery, treatment, or diagnosis of humans), comprising the steps of: forming a laminated structure according to any one of the methods of
[13] to
[15] ; attaching the ultrasonic probe to the skin with the surface on which the ultrasonic coupling material film is formed; and performing an ultrasonic examination.
[0130] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]
[0131] 1...coupling material (membrane), 2...support (release liner), 3...skin, 4...ultrasonic probe; 5...ultrasonic wave; 6...water-soluble gel coupling material; 10...Ultrasound diagnostic device.
Claims
1. An ultrasonic coupling material composition comprising (A) a silicone pressure sensitive adhesive and (B) a silicone oil having no crosslinking points, The silicone pressure-sensitive adhesive (A) comprises a diorganopolysiloxane (a) having a viscosity of 100,000 mPa·s or more at 25°C, R 1 3 SiO 1/2 and SiO 2 Resin having units (R 1 is a hydrogen atom or a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms; and a resin composition (b) containing an organic solvent, The silicone oil (B) having no crosslinking points has a kinetic viscosity at 25° C. of 10 to 100,000 mm 2 Silicone oil having no crosslinking points in the range of / s 1. An ultrasonic coupling material composition comprising:
2. 2. The ultrasonic coupling material composition according to claim 1, wherein the diorganopolysiloxane (a) is a diorganopolysiloxane (a1) having an alkenyl group.
3. 3. The ultrasonic coupling material composition according to claim 2, further comprising, as component (C), an organohydrogenpolysiloxane having a SiH group.
4. 4. The ultrasonic coupling material composition according to claim 3, further comprising a platinum-based catalyst.
5. The ultrasonic coupling material composition according to claim 4, characterized in that the value obtained by dividing the number of moles of SiH groups in the (C) component by the number of moles of alkenyl groups in the (A) component is in the range of 0.5 to 20.
6. 3. The ultrasonic coupling material composition according to claim 2, wherein the component (B) is a linear or branched diorganopolysiloxane having no alkenyl groups or SiH groups.
7. The mass of the (B) component divided by the total mass of the solid content of the (a) component and the (b) component and the (B) component and the (C) component is in the range of 0.2 to 0.
8. The ultrasonic coupling material composition according to claim 3.
8. The ultrasonic coupling material composition according to claim 3, further comprising 0.1 to 10 parts by mass of dry silica per 100 parts by mass of the total of the solid content of the (a) component and the (b) component, the (B) component and the (C) component.
9. An ultrasonic coupling material film comprising a cured product of the ultrasonic coupling material composition according to any one of claims 1 to 8.
10. 10. The ultrasonic coupling material film according to claim 9, wherein the thickness of the ultrasonic coupling material film is in the range of 10 to 10,000 μm.
11. 10. The ultrasonic coupling material film according to claim 9, which is a free-standing film that is separate and independent from a support.
12. A laminated structure comprising a support and the ultrasonic coupling material film according to claim 9 directly on and in contact with the support.
13. A method for forming a laminated structure, comprising: applying the ultrasonic coupling material composition according to any one of claims 1 to 8 onto a release liner film; heating and curing the composition to form an ultrasonic coupling material film; peeling the release liner film from the ultrasonic coupling material film; attaching the ultrasonic coupling material film onto another support; and attaching an ultrasonic probe to the surface opposite to the surface in contact with the other support to form a laminated structure.
14. A method for forming a laminate structure, comprising: applying the ultrasonic coupling material composition according to any one of claims 1 to 8 onto a release liner film; heating and curing the composition to form an ultrasonic coupling material film; and then peeling the release liner film from the ultrasonic coupling material film and attaching the ultrasonic coupling material film to an ultrasonic probe to form a laminate structure.
15. A method for forming a laminate structure, comprising applying the ultrasonic coupling material composition according to any one of claims 1 to 8 onto an ultrasonic probe, and heating and curing the composition to form an ultrasonic coupling material film to form a laminate structure.
16. 15. A method for performing an ultrasonic inspection by attaching the ultrasonic probe to the skin with the surface on which the ultrasonic coupling material film is formed, following the method for forming a laminated structure according to claim 14 (excluding methods for performing surgery, treatment, or diagnosis on humans).
17. 16. A method for performing an ultrasonic inspection by attaching the ultrasonic probe to the skin with the surface on which the ultrasonic coupling material film is formed, following the method for forming a laminated structure according to claim 15 (excluding methods for performing surgery, treatment, or diagnosis on humans).
Citation Information
Patent Citations
JP1971000146U
Ultrasonic coupling material
JP1988019135A
Ultrasound interfacing device for tissue imaging
JP2005532871A
User interfaces for health monitoring
JP2021093127A
Coupling an ultrasound probe to the skin
US9211106B2